Analisis Kesulitan Belajar : Dampak Latar Belakang Kejuruan ditinjau dari Proses Pembelajaran Matematika Perguruan Tinggi - Yasin, Muhammad; Netriwati, Netriwati (Desimal: Jurnal Matematika, 2019)
The purpose of this study is to make a diagnosis of student learning difficulties Mathematics education graduate IPA, IPS and SMK in terms of learning mathematics. This research uses descriptive qualitative research type. Instrument used in the form of interview result, observation result of student learning mathematics and supported by result of questionnaire of interest of student of mathematics education by using Likert scale measurement which used to measure attitude, opinion, or perception of someone about social phenomenon. The results of this study include: (1) Types of learning difficulties for students with science graduates including difficulties in academic learning (academic learning disabilities). (2) Types of learning difficulties students with social studies and vocational backgrounds have a type of learning difficulties related to development (developmental learning disabilities) which includes perceptions, difficulties in language learning and communication, and learning difficulties in adjusting social behavior. (3) the effort that must be made to overcome this is to foster a high interest in learning to students.